2013
DOI: 10.1142/s0219649213500238
|View full text |Cite
|
Sign up to set email alerts
|

Information Searching: The Impact of User Knowledge on User Search Behavior

Abstract: The utilisation of Information and Communication Technology (ICT) and networked information infrastructure in a wide range of businesses and activities has increased the need for fast and reliable information. The information is vital for innovation, competition, and decision making. To date information gathering is no longer absolute from the library, nonetheless the information can be retrieved from all around the world through Internet technology. However, information searching is a tedious process. Knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The behavior of students in seeking information is an action that students take independently to state what information they need and seek that information (Singh, Kumar, & Khanchandani, 2015;Yamin, Ramayah, & Ishak, 2013). The information obtained is then evaluated and will ultimately satisfy the students' needs for that information (Hjorland, 2012;Morrison, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of students in seeking information is an action that students take independently to state what information they need and seek that information (Singh, Kumar, & Khanchandani, 2015;Yamin, Ramayah, & Ishak, 2013). The information obtained is then evaluated and will ultimately satisfy the students' needs for that information (Hjorland, 2012;Morrison, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…As studies have shown, travelling is an activity that interests a wide variety of people [3,4,5,6]. Typically, these people use their prior knowledge on interesting places to search for more information on the Internet [7,8]. Currently, there are several services that allow tourists to find information on the locations they wish to visit [3].…”
Section: Related Applicationsmentioning
confidence: 99%
“…Although children frequently turn to SEs, research has shown that they often experience difficulties in finding resources that satisfy their information needs (Bilal and Gwizdka, 2018; Bilal and Ellis, 2011; Druin et al , 2009; Gossen, 2016). Prior works suggest that this difficulty is often the result of children’s insufficient digital literacy skills (Bilal and Gwizdka, 2018; Hague and Payton, 2011), for example, lack of ability in identifying credible resources when using SEs, in addition to varied degrees of prior experience (Landoni et al , 2019) and domain knowledge (Han, 2017; Yamin et al , 2013). Moreover, children favor resources on the first SERP and barely notice that other SERPs exist (Duarte Torres et al , 2010b; Gwizdka and Bilal, 2017).…”
Section: Background and Related Workmentioning
confidence: 99%